Analisis Perhitungan Biaya Produksi Menggunakan Metode Full Costing Dalam Menentukan Harga Pokok Penjualan Pada Usaha Sulam Benang Emas Di Kota Jambi - Jariyah Widiya Ningsi; Melya Embun Baining; Nurfitri Martaliah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose of this study was to find out how to analyze the calculation of production costs and calculate the cost of goods sold using the full costing method for gold thread embroidery SMEs in Sebrang, Jambi City. The method used in this study is a qualitative method by collecting primary data obtained from observations and interviews. The results of the study showed that gold thread embroidery entrepreneurs in Jambi City did not record the production costs they used. They only rely on memory to measure the amount of spending on production activities. In determining the cost of goods sold, the gold thread embroidery entrepreneur in Jambi City set the selling price based on estimates. After conducting an analysis using the full costing method, it can be clearly seen that the production costs they incur are not in accordance with the actual production costs. This is because gold thread embroidery in Jambi City does not include all elements of production costs, especially factory overhead costs. And in determining the cost of goods sold, it can be seen if the enamel embroidery entrepreneurs across the city of Jambi earn profits above 46% of the production costs incurred.